Photophysical Investigation of One Pot Synthesized Novel Indenofluorene Derivative (BDP) as a Fluorescent Chemosensor for the Detection of Fe3+ Ion - Mohasin, Md; Alam, Md. Zafer; Ahmad, Suhail; Salma, Umme; Kumar, Yogesh; Patel, Rajan; Ullah, Qasim; Khan, Salman A. (Journal of fluorescence, 2025)
An Indane-1-one derivative 11-(1-benzyl-1H-indol-3-yl)-10,12-dihydrodiindeno[1,2-b:2',1'-e]-pyridine (BDP) has been synthesized by the reaction of Indan-1-one with 1-benzyl-1H-indole-3-carbaldehyde. FT-IR, 1 H-NMR, 13 N-NMR and Mass spectroscopic techniques has been used to confirmed the structure of BDP. The observed photophysical changes in BDP across various solvents were associated. The impact of various interactions on photophysical parameters, including Stokes shift, dipole moment, oscillator strength, and fluorescence quantum yields, has been assessed in relation to solvent polarity. Moreover, BDP demonstrates potential as a selective fluorescent chemosensor for detecting Fe 3+ ion within a range of cations in an aqueous DMSO environment. A thorough investigation into the recognition mechanism of BDP towards Fe 3+ ion has been conducted using Benesi-Hildebrand and Stern–Volmer, measurements. BDP forms a 2:1 complex with the Fe 3+ ion, exhibiting fluorescent quenching behaviour.